APPLICATION OF COOPERATIVE LEARNING MODEL WITH JIGSAW TYPE TO IMPROVE LEARNING OUTCOMES OF ISLAMIC RELIGIOUS EDUCATION AND CHARACTER - Ritayanti, Ritayanti; Saguni, Fatimah; Nurdin, Nurdin; Olvianty, Olvianty (Department of Islamic Education, Postgraduate Program Univercity for Islamic Studies Palu, 2024)
This study discusses the implementation of the Jigsaw Cooperative Learning Model to Improve Learning Outcomes. This stufy used as qualitative method. Data were gathered through direct observation, in-depth interview, and written document analysis. In-depth interview involving the school principal, religious teachers, and students. This study found that the Jigsaw cooperative learning method is a form of learning in which students learn and work in small groups collaboratively, with members of 4 to 6 people with a heterogeneous group structure. In forming groups composed of two parts, the first group of origin and the expert group of each participant is responsible for mastering the part of the learning material and can teach the material to the group. The learning step of the jigsaw method consists of 6 activity steps, namely, the teacher divides the class into several study groups. Each group consists of 4-6 students. The teacher provides teaching material in text, which has been divided into several sub-materials for study by each group member. All groups study the teaching material that the teacher has given. Expert groups meet and discuss the material topics for which they are responsible. Expert group members return to their home groups to help their groups. The teacher evaluates student learning outcomes individually. Applying the Jigsaw Learning model is very effective; this can be seen from the positive things done by students, namely getting high grades, being disciplined and responsible, and stimulating students' intellectual curiosity.